FACTORS OF DAMAGE CAUSED BY MOTOR VEHICLES TO THE ENVIRONMENT (British Journal of Global Ecology and Sustainable Development, 2022)
Measures to reduce air pollution associated with automobile emissions have their own specifics. One of the means of reducing air pollution in cities by carbureted cars is the introduction of protective means that reduce the emission of gasoline fumes from the supply system of cars, gas stations, car cisterns. More than 200 kinds of ingredients are formed in motor vehicles during the combustion of fuel. Of these, non-toxic elements that are considered: nitrogen, oxygen, water vapor and carbon dioxide (CO2 - angdric carbonate). Toxic ingredients that pose a danger to human life and the environment are carbon monoxide (CO), nitrogen oxides NxOy, aldehydes, hydrocarbons, sulfur dioxide, carbon black, benz(a)pyrene and others. From the list of toxic wastes, we will mainly consider three ingredients: carbon monoxide (CO), hydrocarbons that have no time to combustion CnHm, nitrogen oxides NOx.